Clinico-genetic heterogeneity in Pakistani families affected with muscular dystrophies - Riaz Ahmad; Muhammad Almas Hashmi; Asad Ullah; Ubaid Ur Rehman; Muhammad Naeem; Henry Houlden (Molecular Biology Reports, 2026)
Background Muscular dystrophies are a group of inherited neuromuscular disorders characterized by degenerative and progressive muscle weakness. Duchenne muscular dystrophy (DMD), Becker muscular dystrophy (BMD) and merosin-deficient congenital muscular dystrophy type 1 (MDC1A) are frequent forms caused by DMD (NM_004006.3) and LAMA2 (NM_000426.4) mutations, respectively. Methods and results Our study used whole exome sequencing to explore the molecular genetics of muscular dystrophies in six unrelated Pakistani families. We found four novel variants in the LAMA2 ; c.7470_7473del; p.(Lys2490AsnfsTer56) in family A, c.7807del; p.(Ala2603HisfsTer4) in family C, c.8651T > C; p.(Met2884Thr) in family D and c.4127T > A; p.(Leu1376Ter) in family E associated with MDC1A in these families. Furthermore, two already cited DMD variants were identified: c.10,801 C > T; p.(Gln872Ter) in family B and hemizygous genomic deletion in DMD (NM_004006.3):g.32438241_32809611del (corresponding to deletion of exons 7–29; GRCh38), which was identified (in family F) associated with BMD and DMD, respectively. Conclusions We present the first report of MDC1A-associated phenotypes caused by the LAMA2 gene in the Pakistani population, while DMD -related cases have already been documented in the literature and public databases. Clinical and molecular diagnosis of these six affected families will be valuable in therapeutic interventions and prenatal diagnosis of neuromuscular dystrophies in the familial and Pakistani populations. Our study emphasizes the effectiveness of next generation sequencing technology over traditional diagnostic methods such as muscle biopsies.

New secondary metabolites and volatile constituents from the leaves of Ocimum gratissimum Linn. - Muhammad Shaiq Ali; Almas Hashmi; Ngoupayo Joseph (Natural Product Research, 2024)

Identification of a novel GLB1 mutation in a consanguineous Pakistani family affected by rare infantile GM1 gangliosidosis - Bibi Zubaida; Muhammad Almas Hashmi; Huma Arshad Cheema; Muhammad Naeem (Journal of Genetics, 2018)